Genome-wide comparative analysis of drought tolerant genes in rice, maize, date palm and arabidopsis - Mohd-Zim, Nurul Asyikin; Sulaiman, Suhaila; Roowi, Siti Habsah; Ahmad Azmi, Nur Sabrina; Zainuddin, Zarina; Samsulrizal, Nurul Hidayah (2021)
The availability of various comparative genomics tools has allowed the identification of several potential drought-tolerant genes in plants such as wheat, tomato, maize and others. In this study, orthologous drought-tolerant genes in Oryza sativa (rice), Zea mays (maize), Phoenix dactilyfera (date palm) and Arabidopsis thaliana (arabidopsis) were identified using InParanoid and SonicParanoid tools. From the 9,952 orthologous proteins found among the four species, 8,573 sequences were annotated and assigned to 5,729 GO terms; classified into the biological process category, molecular function category and cellular component category. Sixty-five OGs were found to be represented under four drought tolerance GO terms; regulation of response to water deprivation (GO:2000070), response to water deprivation, behavioural response to water deprivation (GO:0042630), and cellular response to water deprivation (GO:0042631). The potential drought tolerance genes have been predicted by using sequence homology search against the Drought Stress Gene Database (DroughtDB). Three potential drought-tolerant genes were selected and visualised to compare the gene alignment across the 4 species using the MAUVE software. To assure a satisfactory outcome, this in silico study will be confirmed by genome editing studies in rice via CRISPR/Cas9 system.